Recommended reference materials for the realization of physicochemical properties - Marsh, K. N. (India Vikas, 1991)
This definitive volume, containing contributions from internationally acclaimed experts, provides a comprehensive review of the various materials which can be used as references for checking the correct operation or for the calibration of equipment used for physicochemical measurement. The important areas covered include density, viscosity, enthalpy, thermal and electrolytic conductivity, optical rotation and refraction, and relative molar mass. It will become an essential reference text for all physical and analytical chemists and chemical engineers, and those working in standards laboratories.